Phosphorus-31 and carbon-13 nuclear magnetic resonance study of glucose and xylose metabolism in agarose-immobilized Candida tropicalis. - Lohmeier-Vogel, E M (1995)
Candida tropicalis can ferment both hexose and pentose sugars. Here, we have used 31P and 13C nuclear magnetic resonance spectroscopy to study the capacity of this yeast species to metabolize glucose or xylose when immobilized in small (< 1-mm-diameter) agarose beads. Immobilized C. tropicalis metabolizing glucose showed rapid initial growth within the beads. A corresponding drop in the intracellular pH (from 7.8 to 7.25) and hydrolysis of intracellular polyphosphate stores were observed. Although the initial rate of glucose metabolism with immobilized C. tropicalis was similar to the rate observed previously in cell suspensions, a decrease by a factor of 2.5 occurred over 24 h. In addition to ethanol, a significant amount of glycerol was also produced. When immobilized C. tropicalis consumed xylose, cell growth within the beads was minimal. The intracellular pH dropped rapidly by 1.05 pH units to 6.4. Intracellular ATP levels were lower and intracellular Pi levels were higher than observed with glucose-perfused cells. Consumption of xylose by immobilized C. tropicalis was slower than was previously observed for oxygen-limited cell suspensions, and xylitol was the only fermentation product.